Refrigeration Systems and Applications 2019 - Aprea, Ciro (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue "Refrigeration Systems and Applications" aims to encourage researchers to address the concerns associated with climate change and the sustainability of artificial cold production systems, and to further the transition to the more sustainable technologies and methodologies of tomorrow through theoretical, experimental, and review research on the different applications of refrigeration and associated topics.